The effect of habitat change on the structure of dung beetle assemblages in the north-eastern Free State : a comparison of conserved and farmed land - Scholtz, Clarke H. (University of Pretoria, 2013)
Thesis (PhD (Entomology))--University of Pretoria, 2006.